Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2021)
A dataset containing 340652 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is one of (Cerastium fontanum subsp. lucorum (Schur) Soo, Cerastium glomeratum Thuill., Crepis pyrenaica (L.) Greuter, Dactylorhiza maculata subsp. fuchsii (Druce) Hyl., Dactylorhiza maculata subsp. fuchsii (Druce) H.Sund., Epilobium alsinifolium Vill., Epilobium alsinifolium Blytt, Epilobium tetragonum subsp. lamyi (F.W.Schultz) Nyman, Epilobium tetragonum f. lamyi (F.W.Schultz) Rouy & E.G.Camus, 1901, Euphrasia rostkoviana Hayne, Geranium robertianum f. purpureum (Vill.) Rouy, Geranium robertianum subsp. purpureum (Vill.) Murb., Geranium robertianum subsp. purpureum (Vill.) Nyman, Geranium robertianum subsp. purpureum Schur, Geranium robertianum var. purpureum (Vill.) DC., Geranium robertianum var. purpureum (Vill.) Pauquy, Geranium robertianum var. purpureum Cariot & St.-Lag., 1889, Geranium robertianum var. purpureum Mill., Geranium robertianum var. purpureum Mill. ex Nyman, Geranium robertianum var. purpureum Schur, Glechoma hederacea subsp. hirsuta (Waldst. & Kit.) F.Herm., 1912, Glechoma hederacea subsp. hirsuta (Waldst. & Kit.) Gams, Glechoma hederacea var. hirsuta (Waldst. & Kit.) P.Fourn., 1961, Glechoma hederacea var. hirsuta Coss. & Germ., Leontodon hispidus var. pseudocrispus Sch.Bip. ex Bisch., Leontodon hispidus subsp. pseudocrispus (Bisch.) Greuter, 2003, Leontodon hispidus subsp. pseudocrispus (Sch.Bip. ex Bisch.) Gremli, 1885, Leontodon hispidus subsp. pseudocrispus (Sch.Bip. ex Bisch.) Murr, Leontodon hispidus var. pseudocrispus (Sch.Bip. ex Bisch.) Lambinon, 2004, Leontodon hispidus var. pseudocrispus Sch.Bip., Pinus mugo var. uncinata (Ramond ex DC.) Fiori, Pinus mugo subsp. uncinata (Ramond ex DC.) Domin, Plantago major subsp. intermedia (DC.) Arcang., Plantago major f. intermedia (Gilib.) Pilg., Plantago major f. intermedia (Gilib.) Rouy, 1908, Plantago major subsp. intermedia (DC.) Lange, Plantago major var. intermedia (DC.) Pilg., Plantago major var. intermedia (Gilib.) Ces., 1874, Plantago major var. intermedia (Gilib.) Noulet, 1837, Plantago major var. intermedia Decne., 1852, Pyrola chlorantha Sw., Salix myrsinifolia Salisb., Saxifraga exarata subsp. moschata (Wulfen) Cavill., Silene vulgaris subsp. glareosa (Jord.) Marsden-Jones & Turrill, Tragopogon pratensis subsp. minor (Mill.) Hartm., Tragopogon pratensis subsp. minor (Mill.) Wahlenb., Tragopogon pratensis var. minor Willk., Tragopogon pratensis subsp. orientalis (L.) Celak., Tragopogon pratensis var. orientalis Schmalh., Vicia cracca subsp. incana (Gouan) Rouy, Vicia cracca var. incana Burnat, 1896, Vicia cracca f. tenuifolia (Roth) Gaudin, Vicia cracca subsp. tenuifolia (Roth) Bonnier & Layens, Vicia cracca subsp. tenuifolia (Roth) Corbière, Vicia cracca subsp. tenuifolia (Roth) Gaudin, Vicia cracca var. tenuifolia (Roth) Beck, Vicia cracca var. tenuifolia (Roth) G.Gaertn., B.Mey. & Scherb., 1801, Viscum album var. austriacum (Wiesb.) Beck, 1892, Viscum album subsp. austriacum (Wiesb. ex Dichtl) Vollm.)", "Geometry POLYGON((-9.36035 44.71551,-10.59082 42.81152,-11.82129 36.80928,-7.69043 36.17336,-3.38379 35.88905,3.12012 38.13456,9.18457 38.20366,11.7334 37.16032,12.78809 34.74161,17.09473 33.79741, 23.15918 34.23451,30.10254 32.62087,33.2666 32.99024,35.72754 35.03,33.00293 35.53223,28.69629 35.17381,28.34473 36.31513,25.7959 37.50973,24.91699 39.90974,28.78418 40.6473,30.71777 41.17865,36.87012 45.213,38.18848 46.98025,38.71582 47.7541,39.94629 47.93107,40.20996 49.61071,37.0459 50.34546,35.72754 50.40152,33.79395 52.26816,31.68457 51.94426,31.4209 53.27835,32.56348 53.43572,30.98145 54.77535,30.89355 55.52863,28.43262 56.02295,27.20215 57.65716,27.37793 58.30949,27.90527 59.17593,29.66309 59.88894,27.6416 60.58697,31.50879 62.75473,28.78418 69.83962,30.89355 70.28912,29.22363 71.55274,21.75293 71.30079,14.28223 70.14036,11.38184 67.47492,4.87793 63.66576,-5.53711 71.52491,-10.63477 71.69129,-21.5332 67.74276,-28.56445 65.36684,-24.3457 61.35461,-9.36035 44.71551))", "HasCoordinate is true", "HasGeospatialIssue is false", "Year is greater than or equal to 1980", "Year is less than or equal to 2020" ] } The dataset includes 340652 records from 550 constituent datasets: 1 records from Biosphärenpark Wienerwald - Pfaffstätten. 4 records from Données naturalistes de Paul ROUVEYROL. 2 records from Herrensee-Gebiet (Fischbachtal im Odenwald). 5 records from Application INPN Espèces: Observations naturalistes, participatives et opportunistes, fondées sur des photographies. 887 records from Welsh BSBI data (ex-VPDB dataset) at hectad resolution. 1 records from Inventaire du site Pierre Fabre de Cahors. 1 records from Données espèces - Expertise IQE 89. 15 records from Jeu de données convention FEGVE-SPN-2012-2016. 134 records from Steiermärkisches Landesmuseum Joanneum - Herbarium GJO. 1 records from Données naturalistes de RAYNARD Philippe. 1 records from InboVeg - Amphibious vegetation of shallow lakes at Turnhout. 1 records from Royal Botanic Garden Edinburgh Living Plant Collections (E). 1 records from Community Foundation for Ireland Records. 1 records from Patrick Roper’s Notebooks. 13 records from Botany registration database by Danish botanists. 7 records from Inventaire de la flore de la Vienne 2013. 6 records from Carnet B Centre - lot 2012. 2 records from Inventaire de la réserve zoologique de la Haute Touche (Indre). 34 records from Inventaires du Conservatoire botanique national méditerranéen dans le cadre de l'ATBI Mercantour.. 1 records from Projekt Dellbrücker Heide. 111 records from Inventaire de la flore des Pyrénées-Atlantiques 2018. 2315 records from The Danish Environmental Portal, species and habitats-database "Danmarks Miljøportals Naturdatabase". 16542 records from BSBI data from several English counties, up to 2015. 60 records from University of Vienna, Institute for Botany - Herbarium WU. 3 records from Biodiversity mapping in connection with Nature in Norway (NIN) in Troms and Finnmark, Norway (2018). 2 records from Lustadter Wald .. 1 records from Birdrace-Die_Nachtraben-Stuttgart. 2 records from Artenvielfalt des "Grünen Klassenzimmers". 1 records from Données espèces Expertise IQE 311. 1 records from Museu de Ciències Naturals de Barcelona: BGJBB. 138 records from Colección de plantas vasculares del Herbario "Jaime Andrés Rodríguez". LEB. 41 records from Cartographie des Leguminosae (Fabaceae) en France. 129 records from Finnish Floristic Database (Vascular plant data of Kevo Subarctic Research Institute). 1 records from GEO Biodiversity Day. 2 records from Isle of Man Historical Wildlife Records pre-1990. 1 records from Botany (UPS). 1 records from Inventaire de la flore de Dordogne 2014. 4 records from Inventaire de la flore de la Communauté Urbaine de Bordeaux 2009. 558 records from Herbarium Berolinense, Berlin (B). 1 records from Vom Gipfel ins Moor, Transekt im NSG Allgäuer Hochalpen. 31 records from Inventaire de la flore des Pyrénées-Atlantiques 2017 - Littoral. 35 records from Inventaire de la flore de Charente-Maritime 2015. 11 records from Vegetation releves in 150 grassland EPs in 2008. 14 records from Carnet B Lorraine. 1180 records from Flora of Worcestershire. 1 records from Rund um das LUGY. 6 records from Données naturalistes de GAULTIER Cyrille. 23 records from Fungus Collections at Staatliches Museum für Naturkunde Karlsruhe (Herbarium KR). 1 records from Waldränder der Frankenhöhe (Rothenburg ob der Tauber). 2 records from PAMP-tracheo: Vascular plants in Pamplona Basin (Navarra, Spain). Undergraduate thesis, D. Vicente. 13 records from flower availability 2008 Alb-korrigiert. 1 records from Schulgelände IGS Kaufungen. 37 records from University of Graz, Institute of Plant Sciences - Herbarium GZU. 252 records from Inventaire de la flore de Gironde 2016. 2 records from TransForest - vegetation, lichen and fungi data 2016. 139 records from Inventaire de la flore des Landes 2016. 1 records from Données naturalistes de CERCOPE (Jean-Louis PRATZ). 131 records from Inventaire de la flore de Dordogne 2018. 3 records from Biowide Species data. 9 records from Herbario de la Universitat de les Illes Balears. 1 records from renaturierter Main (Kemmern bei Bamberg). 52 records from SER Site-based Surveys. 1 records from Schanzenanlage Bergham. 10 records from Atlas de la flore de Lorraine. 453 records from Vascular plant herbarium TRH, NTNU University Museum. 235 records from Oskarshamn herbarium (OHN). 698 records from Observational database of Icelandic plants. 7 records from Nijmegen Natural History Museum (NL) - Herbarium. 2 records from Convention Fédération française de golf - MNHN 2016-2019.. 2288 records from Estonian Naturalists’ Society. 2434 records from Suffolk Biodiversity Information Service (SBIS) Dataset. 1 records from Données d'observation flore du réseau des CBN issues du système d'information de la FCBN. 2 records from GEO-Hauptveranstaltung in "Wildtierland". 1 records from Spredning av fremmede arter med tømmerimport til Norge. 1 records from Welsh Invertebrate Database (WID). 1 records from Dierloch, nördlicher Mooswald (Freiburg-Hochdorf). 1633 records from Banco de Datos de la Biodiversidad de la Comunitat Valenciana. 17 records from Miscellaneous Vascular Plants. 2 records from University of Alberta Vascular Plant Herbarium (ALTA-VP). 234 records from Masaryk University - Herbarium BRNU. 1 records from Long-Term Monitoring Network Vegetation Quadrats. 2 records from Fuldaaue (Stadtgebiet Fulda). 1 records from Inventaire des pelouses calcicoles du PNR du Marais Poitevin 2017. 104 records from Segetal flora of Italy. 140 records from CeDoc de Biodiversitat Vegetal: BCN-Cormophyta. 4357 records from Atlas Flora Danica. 6 records from Isle of Man historical wildlife records 1995 to 1999. 2 records from BoBO - Botanic Garden and Botanical Museum Berlin Observations. 46 records from RHS monitoring of native and naturalised plants and animals at its gardens and surrounding areas. 1 records from Monitoring data from the federal state Saxony-Anhalt (Germany). 1 records from Schlattstaller Tal (Lenningen). 218 records from Inventaire permanent de la flore du massif armoricain. 150 records from Finnish Floristic Database (Literature Sources). 1583 records from naturgucker. 3 records from Survey and monitoring records for Scottish Wildlife Trust reserves from reserve convenors and Trust volunteers - Verified data. 743 records from iNaturalist Research-grade Observations. 2 records from GEO-Hauptveranstaltung (Duisburg). 72 records from Flora of Słowiński National Park, Poland. 334 records from Environmental Monitoring Database Species data 1987 to 2015. 3 records from Données naturalistes de Xavier JAPIOT. 418 records from Vascular plant records verified via iRecord. 14 records from Données naturalistes de Pascal AMBLARD. 1 records from Species of plants, fungi and animals from separate territories of Podesinnia. 7 records from Gipuzkoako Foru Aldundiaren Landareen Germoplama Bankua / Banco de Germoplasma Vegetal de la Diputación Foral de Gipuzkoa. 1 records from RNF - LPO Rhône-Alpes. 14 records from Universitat de Girona: HGI-Cormophyta. 3 records from Monitoring data from the federal state Bavaria (Germany). 247 records from Colección de plantas vasculares del herbario de la Universitat de València (VAL). 82 records from All taxa records for Leicestershire and Rutland. 20 records from Inventaire de la flore de Charente-Maritime 2014. 75 records from Wikiplantbase #Sardegna. 1 records from Wälder bei Nordkirchen. 4 records from NINA Artskart data. 1 records from Gemeindegebiet Weikendorf (Marchfeld). 1 records from Naturschutzgebiet Bausenberg. 11 records from Herbarium (AMNH). 9 records from RNF - Données du Parc Naturel Régional du Vercors. 4 records from GEO Hauptveranstaltung Tirol (Innsbruck). 37 records from Catálogo Florístico Histórico de Navarra. Gobierno de Navarra. 2 records from University of South Carolina, A. C. Moore Herbarium. 10 records from Natural History Museum Rotterdam - Specimens. 5 records from Vascular plants of Amrum 2007-2008. 1 records from InboVeg - NICHE-Vlaanderen groundwater related vegetation relevés for Flanders, Belgium. 41 records from MGC Herbarium of University of Malaga (Spain): MGC-Cormof dataset. 1 records from Erzental (Oberotterbach). 1 records from Landschaftsschutzgebiet Eulenkopf (VG Otterbach). 17 records from Inventaire de la flore des Landes 2014 (Littoral dunaire). 114 records from Herbario HSS Finca La Orden-Valdesequera (CICYTEX). Junta de Extremadura. 45 records from Phase 2 Lowland Grassland Survey of Wales. 15 records from Jeux de données provenant de l'ATBI Mercantour. 27 records from Inventaire de la flore des Pyrénées-Atlantiques 2017. 1 records from Bayerische Donau - Neu Ulm. 1 records from Inventaires PnrL "Etangs". 14 records from Universidad de Oviedo. Departamento de Biología de Organismos y Sistemas: FCO-Briof. 10 records from Herbarium Senckenbergianum (FR). 4 records from Inventaire de la flore des ENS des Pyrénées-Atlantiques 2011-2012. 8 records from Merseyside BioBank Active Naturalists (unverified). 3 records from MBM - Herbário do Museu Botânico Municipal. 168 records from Leicestershire and Rutland Environmental Records Centre records 2015-2019. 3 records from Vascular Plants, Museum of Archaeology, University of Stavanger. 3 records from CeDoc de Biodiversitat Vegetal: BCN-Seeds. 147 records from Données naturalistes de Pierre DUFRENE. 1 records from Freigelände Naturschutzscheune Reinheimer Teich (Kreis Darmstadt-Dieburg). 1 records from Hainhoop - Tonkuhle - Bullenmoor (Arpke). 11 records from Inventaire de la flore de Charente 2013. 5 records from Ecofact. 28 records from ArtenFinder. 1 records from Schulgarten mit Klasse 8a (Essen). 98 records from Dorset Sites of Nature Conservation Interest (SNCI) species records pre 2000. 1 records from IPS Golfs. 10 records from Herbario de la Facultad de Farmacia de la Universidad Complutense de Madrid (MAF). 387 records from Fermanagh Flora. 2 records from University of British Columbia Herbarium (UBC) - Vascular Plant Collection. 6 records from RNF - Données de l'association Vivarmor Nature. 2 records from Stackpole National Nature Reserve Species Inventory and Ad-hoc Sightings from Across Pembrokeshire. 169 records from Isle of Man wildlife records from 01/01/2000 to 13/02/2017. 129 records from Inventaire de la flore des Landes 2018. 5 records from Radnorshire Wildlife Trust records held by BIS. 178 records from Données naturalistes de Thomas GAILLARD. 2516 records from Pl@ntNet automatically identified occurrences. 1 records from Schulhofuntersuchung Thomas-Mann-OS. 1 records from Tag der Artenvielfalt. 27 records from Stabbetorp - Floristiske registreringer 2016. 9 records from Species recordings from the Danish National portal Arter.dk. 12 records from FloVegSI - Floristical and fitocenological database of ZRC SAZU. 28 records from Données faune, flore et fonge du Conservatoire des espaces naturels du Nord Pas-de-Calais. 9791 records from Florabank1 - A grid-based database on vascular plant distribution in the northern part of Belgium (Flanders and the Brussels Capital region). 1 records from Rund um den Eichwald,Schulhof Friedrich Fröbel Gymnasium- Bad Blankenburg. 8 records from Northern Ireland Environment Agency (NIEA) Collated Species Records. 27 records from R.H.Wardell - Cardiff Nature Conservation Strategy - 1991 - 1998. 209 records from Données de la flore d’Alsace (SBA). 1 records from Sbp-BioBlitz2017_60years-BiodiversityData. 43 records from NRW Regional Data: South East Wales Non-sensitive species. 108 records from National Trust Species Records. 1 records from PAMP-tracheo: Vascular plants in La Demanda and Cameros mountain ranges (La Rioja, Spain). PhD project, L.M. Medrano. 101 records from Natagriwal ; Observations made from operations within Natura 2000 habitats and other semi-natural areas. 79 records from Waarnemingen.be - Non-native plant occurrences in Flanders and the Brussels Capital Region, Belgium. 1 records from Bayerische Donau - Blindheim Donaubrücke. 8 records from Inventaire de la flore du Grand Poitiers 2009. 87 records from Estonian Museum of Natural History Department of Botany. 10 records from flower availability 2007 Schwäbische Alb. 13 records from RNF - Données du Conservatoire d'espaces naturel Centre. 2 records from NRW Regional Data: North Wales. 1 records from Données espèces - Expertise IQE 45. 2518 records from LERN Records. 39 records from Miscellaneous records held on the Cofnod database. 45 records from Inventaire de la flore des Pyrénées-Atlantiques 2007-2008 - Littoral. 1606 records from Vascular Plant Herbarium, Oslo (O) UiO. 57 records from Vascular Plant Records up to 2010. 1 records from Woodmeadow Botanical Survey 2018. 14138 records from Observation.org, Nature data from around the World. 2 records from MBM herbarium - Museu Botânico Municipal \ Curitiba - Herbário Virtual REFLORA. 63 records from Inventaire de la flore des Landes 2012 (Chalosse et Tursan). 1 records from Wald und Wiese am Buchwald. 41 records from Inventaire de la flore de Charente-Maritime 2012. 57 records from ARKO kulturmarkseng. 1 records from Données espèces - Expertise IQE 308. 1 records from iNaturalist records from Northern Ireland. 99 records from Inventaire de la flore des Pyrénées-Atlantiques 2015. 43 records from Inventaire de la flore du PNRLG 2016 (Gironde). 40 records from vegetation releves on grassland gridplots in 2007. 10 records from Jeu de données convention Eurovia-SPN-2012-2016. 1 records from Artenvielfalt Kreis Gießen. 182 records from Biologiezentrum Linz. 5 records from RNF - Données de l'association ASTERS. 596 records from Vascular plant herbarium, UiT Tromsø Museum. 20 records from Charles University Prague - Herbarium PRC. 46 records from Herbarium of the Department of Natural Forests (Forest Research Institute) - Plants. 2 records from Vascular Plants, Observations, Oslo (O). 73 records from Inventaire de la flore de Charente-Maritime 2016. 1 records from UTEP Plants (Arctos). 4 records from Herbarium (ICEL). 2 records from Schussenaue (Weingarten). 2 records from University of Tartu Natural History Museum and Botanical Garden Botanical Collections. 20 records from Conventions d’étude sur la biodiversité française – Partenariats du Service du patrimoine naturel. 6 records from RNF - Données de la Communauté de Communes de Gevrey Chambertin. 7 records from Photographs of higher plants, mosses, fungi, lichens, and algae. 1 records from Taxon occurrence data for the FungalRoot database. 4 records from Brecknock Wildlife Trust (Now WTSWW Brecknockhire) records held by BIS. 1 records from Données espèces - Expertise IQE 46. 69 records from Inventaire de la flore du Pays Bassin d'Arcachon - Val de l'Eyre 2010-2013. 3 records from Grassland Survey of Lochaber 1990-94. 3 records from Données naturalistes de Julien BIRARD [Inventaire Eclair 18 juin]. 1 records from Innenstadt Göttingen - Natur Zuhause. 2796 records from Biodiversitätsdatenbank Salzburg. 1 records from Artenvielfalt im Beckerbruch (Dessau). 15 records from flower visitor interactions 2008. 5 records from Kartlegging av dragehode. 56 records from Vascular plants in power line clearings and the nearby forest, southeast Norway. 44 records from Herbario de la Facultad de Ciencias Biológicas de la Universidad Complutense de Madrid (MACB). 142 records from VIT Herbarium - Vascular Plants (The Natural History Museum of Alava). 64 records from Inventaire de la flore de Charente-Maritime 2018. 61 records from Inventaire de la flore de Lot-et-Garonne 2014. 11 records from Inventaire de la flore des Deux-Sèvres 2015. 13 records from Digitization of plant specimens from Rhoen and Vogelsberg (FULD). 66 records from Montgomeryshire Wildlife Trust records held by BIS. 1 records from Bayerische Donau - Leipheim. 3 records from NMNH Extant Specimen Records. 36 records from Données RNF - PNR des ballons des Vosges. 2 records from Royal Botanic Gardens, Kew - Herbarium Specimens. 58 records from Wikiplantbase #Liguria. 1 records from Biotope auf dem Gelände der Eggerstedt- Kaserne in der Nachbarschaft der Theodor-Heuss-Schule. 1 records from Umgebung der Gesamtschule Winterhude (Hamburg). 5 records from Données de la base Ecosphère. 16 records from Vascular Herbarium, NMBU. 4 records from Données Herbiers de l'Université de Strasbourg. 362 records from Données acquises dans le cadre de l'activité du bureau d'étude BIOTOPE (1994 - 2013). 9083 records from Other BSBI Scottish data up to 2015. 1 records from Données naturalistes acquises sur les sites du MNHN. 7 records from Biodiversity4all Research-Grade Observations. 23 records from Yorkshire Wildlife Trust - Non-sensitive records from all taxonomic groups. 1 records from Obstwiese Osterberg. 56 records from Aranzadi Zientzi Elkartea. 119 records from Inventaire de la flore de Lot-et-Garonne 2017. 112 records from Trondheim urban biodyversity survey. 3 records from RNF - Données du Syndicat de Gestion des Gorges de l'Ardêche. 14528 records from Occurrence Data of Vascular Plants collected or compiled for the Flora of Bavaria. 2 records from Données espèces - expertise IQE 110. 3 records from Unna-Mühlhausen, Wiesen. 28 records from Isle of Man historical wildlife records 1990 to 1994. 31901 records from INPN - Données flore des CBN agrégées par la FCBN. 54 records from TWIC Biodiversity Field Trip Data (1995-present). 7 records from Vascular Plants, Field notes, Agder naturmuseum (KMN). 1 records from Données espèces _ Expertise IPE 16. 373 records from Biodiversitätsdatenbank Nationalpark Hohe Tauern. 84 records from Argyll Biological Records Dataset. 125 records from Natural Resources Wales Regional Data : Mid-Wales. 19 records from Données Saint-Gobain Distribution Bâtiment France. 7 records from Staffordshire Wildlife Trust Nature Reserves Inventory. 11 records from Dorset SSSI Species Records 1952 - 2004 (Natural England). 1 records from Pilstingermoos. 3 records from Herbarium specimens of Jardins botaniques and Conservatoire Botanique of Nancy (NCY). 2 records from Merseyside BioBank Active Naturalists (verified). 2 records from Naturschutzgebiet Lüneburger Heide. 114 records from Tiroler Landesmuseum Ferdinandeum. 246 records from Collections and observation data National Museum of Natural History Luxembourg. 21 records from Données naturalistes de Pierre HUGUENY. 220 records from Natural History Museum, Vienna - Herbarium W. 8 records from Vegetation surveys of coastal shingle in Great Britain. 24 records from EDP Foz-Tua: Vascular Flora – Complementary Studies and Baseline Year of the Ecological Monitoring Program [2011]. 9 records from flower visitor interactions 2007 Schwäbische Alb. 3 records from Données naturalistes de Rose-Line PREUDHOMME. 178 records from Inventaire de la flore du PNRLG 2018 (Landes). 2 records from Gemeinde Sursee. 30 records from NBIS Records to December 2016. 70 records from Merseyside BioBank (unverified). 389 records from Atlas des plantes vasculaires de Lorraine. 1 records from Industriegebiet (Kempen). 17 records from DIBA-Parc del Montnegre i el Corredor. 1 records from Biologische Station im Kreis Wesel. 14 records from INSDC Sequences. 23 records from Données naturalistes de Damien AVRIL. 174 records from Inventaire de la flore de Dordogne 2017. 40 records from Herbario ABH (Universidad de Alicante). 9436 records from Observations du Conservatoire botanique national du Bassin parisien.. 1 records from NABU Naturschutzhof Netttetal (Sassenfeld) e.V.. 11 records from Tidlig oppdagelse og varsling av fremmede arter 2019. 3 records from Perchtoldsdorfer Heide. 95 records from Leicestershire and Rutland Environmental Records Centre records 2000-2009. 3 records from Inventaire de la flore de la Vienne 2014. 2 records from Bulau. 79 records from Inventaire de la flore de Charente-Maritime 2017. 498 records from RECORD Vascular Plant Data. 3 records from Données naturalistes de Ségolène FAUSTEN. 3 records from Faun. 1 records from Schlern - (Bozen). 4 records from Museu Darder de Banyoles. 26 records from Données naturalistes de Cyril EPICOCO. 36203 records from Artportalen (Swedish Species Observation System). 7659 records from Norwegian Species Observation Service. 9362 records from Floristic records from survey studies of the Bayerisches Landesamt für Umwelt. 7781 records from Observations floristiques issues de la base de données du Conservatoire botanique national alpin. 1 records from Données naturalistes d'Anaïs MAS. 55 records from Wikiplantbase #Emilia-Romagna. 925 records from Vascular Plants, Field notes, Oslo (O). 136 records from Records of vascular plants, bryophytes and lichens from Ukrainian Grassland Database. 23 records from Tallinn Botanic Garden. 22 records from Naturalis Biodiversity Center (NL) - Botany. 1 records from City of Edinburgh Natural Heritage Service - Ranger Ad-hoc records and sightings. 125 records from Manscape. 1 records from The Fungal Collection of Helga Große-Brauckmann at the Botanische Staatssammlung München. 518 records from Wikiplantbase #Toscana. 97 records from Inventaire de la flore des Pyrénées-Atlantiques 2016. 854 records from Relevés floristiques du protocole de l'Inventaire National Forestier de l'IGN. 2 records from Artenvielfalt auf der Weide - GEO-Hauptveranstaltung in Crawinkel. 18 records from Dutch Foundation for Applied Water Research (STOWA) - Limnodata Neerlandica. 599 records from BioFokus. 33 records from Données Vigie-Flore. 1 records from BUND - Dassower See (Lübeck/Dassow). 112 records from A common plants survey of vascular plants in South Northumberland and Durham, United Kingdom. 227 records from Inventaire de la flore des Landes 2015. 1 records from Données naturalistes d'Océane ROQUINARC'H. 163 records from Inventaire de la flore de Lot-et-Garonne 2018. 33 records from Naturhistorisches Museum Mainz, Feldbeobachtungsdaten Pflanzen. 71 records from Herbarium Universitatis Daugavpiliensis. 1 records from Leben im Finkensteiner Moor. 9 records from Herbarium Horti Botanici Pisani (PI), Sistema Museale di Ateneo, Università di Pisa. 10 records from Occurrence data from various smaller projects in Norway. 1 records from Plants, Bryophytes and Lichens recorded on the Nevis Estate during summer 2003.. 32 records from International Barcode of Life project (iBOL). 2 records from Schulzentrum "Parc Hosingen". 1421 records from BRERC species records from all years at full resolution excluding Notable Species within the last 10 years. 130 records from Hatikka Observation Database. 38 records from Données naturalistes d'Olivier ESCUDER. 3 records from Données naturalistes de AUNEAU Florent. 406 records from EDP Foz-Tua: Vascular Flora and Habitats – Ecological and Complementary Measures Monitoring Programs – Construction Phase II [2015-2016] and Flooding Phase [2016-2017]. 217 records from inatura - Erlebnis Naturschau Dornbirn. 37 records from Finnish Floristic Database (Åbo Akademi University Collections). 1289 records from Données d'occurrences Espèces issues de l'inventaire des ZNIEFF. 11646 records from Finnish Floristic Database (Finnish Museum of Natural History Collections). 24 records from Images and observations of mostly edible plants in Stephen Barstow’s Edible Garden in Norway, taken between 2005 and 2014. 1 records from Streuobstwiesengelände St.Meinrad Gymnasium. 104 records from Données naturalistes flore et fonge du Conservatoire des espaces naturels Auvergne saisies avant le 18 février 2019.. 467 records from Floristic Databases of Mecklenburg-Pomerania - Higher Plants. 7 records from RNF - Données du Conservatoire d'espaces naturel Limousin. 1 records from Shire Group IDB species data 2004 to present. 26 records from Inventaire de la flore de Lot-et-Garonne 2013. 195 records from Inventaire de la flore de Gironde 2018. 1 records from RNF - Données de l'Association GEREPI (GEstion de la REserve naturelle nationale du PInail). 4 records from Herbario de Universidad de Murcia: MUB. 1 records from Geo-Tag der Artenvielfalt Süßen Hornwiesen-Grundschule. 23 records from Manx Biological Recording Partnership VERIFIED Isle of Man records between 14/02/2017 and 05/09/2019. 1 records from Frau Voss. 188 records from Observations occasionnelles Parc national des Pyrénées. 15 records from Moscow University Herbarium (MW). 89 records from Inventaire de la flore du PNRLG 2017 (Landes). 93 records from National Plant Monitoring Scheme - England, Scotland, Wales. 1 records from Artskartlegging flomsikringstiltak, Kvam 2013. 1 records from 2017 North Devon Area of Outstanding Natural Beauty (AONB) Combe Martin Devon Bioblitz. 168 records from EDP Foz-Tua: Macrophytes – Ecological Monitoring Program [2011-2015]. 1 records from Données espèces - Expertise IQE 88. 6 records from WTSWW Data: All Taxa (West Wales). 3 records from GEO-Hauptveranstaltung (NLP Harz / Hochharz). 1435 records from Cartografía de vegetación a escala de detalle 1:10.000 de la masa forestal de Andalucía. 1 records from Kühmark bei Wetzlar. 2 records from Spredning av fremmede arter med planteimport til Norge. 15 records from Herbarium of Umeå University (UME). 35 records from Dorset Sites of Nature Conservation Interest (SNCI) species records 2000-2008. 2 records from Flore Bord de route/CG55 - Parc Naturel régional Lorraine. 98 records from Karplanter i vernet barskog og edelløvskog. 3 records from Inventaire de la flore de la Vienne 2015. 7 records from Jardín Botánico Atlántico, Gijón: JBAG. 1 records from Schlichemquelle (Tieringen/Meßstetten). 1 records from InsectScale2008FlowerCover. 1 records from Données espèces - Expertise IQE 119. 210 records from Inventaire de la flore de Dordogne 2015. 1 records from Lowland lakeshore vegetation in Nord-Trøndelag, Norway. 46 records from Gloucestershire Historic Wildlife Sightings prior to 1st Jan 2000. 83 records from Estonian University of Life Sciences Institute of Agricultural and Environmental Sciences Vascular Plant Herbarium. 1 records from Convention Suez Environnement (SITA) – SPN. 29 records from Universität Salzburg. 1946 records from Observations faune et flore du Parc national des Écrins. 32 records from Ireland's BioBlitz. 1 records from LaBoOb02. 20 records from Dr Mary Gillham Archive Project. 11 records from Commissioned surveys and staff surveys and reports for Scottish Wildlife Trust reserves - Verified data. 773 records from Hertfordshire Flora Survey Records 1987-2005. 360 records from Données ONF faune-flore-fonge. 5 records from Stoke-on-Trent Environmental Survey results (1982-1984). 2 records from Sudeniederung (Amt Neuhaus), Landkreis Lüneburg. 1 records from Isarufer. 2 records from FLORUS: miscellaneous records. 45 records from vegetation releves on grassland gridplots 2007-2009. 1 records from Données espèces - Expertise IPE 70. 50 records from Institut Botanic de Barcelona (IBB, CSIC-Ajuntament de Barcelona), BC-Plantae. 8 records from Estonian Nature Observations Database. 1 records from Landschaftsschutzgebiet Hexenberg (Erftstadt-Erp). 254 records from Inventaire de la flore de Gironde 2015. 262 records from Herbarium Willing at Herbarium Berolinense, Berlin (B). 65 records from Geneva Herbarium – General Collection (G). 32 records from Herbarium of Jyväskylä University Museum. 56 records from Données acquises via le réseau du Conservatoire botanique national du Bassin parisien. 1 records from RNF - Données du Conservatoire d'espaces naturel Franche-Comté. 1 records from Grünes Germersheim. 1 records from Orchideenstandort Nostengraben - Kretzberg (Oßmaritz). 1 records from Indicateur Petits Sites SUEZ. 1 records from Deponie Klausdorf. 2 records from Jardín Botánico Atlántico, Gijón: JBAG-Laínz. 2 records from Royal Botanic Garden Edinburgh Herbarium (E). 156 records from CSIC-Real Jardín Botánico-Colección de Plantas Vasculares (MA). 1 records from Erlengraben/Lipp-Tal (Östringen). 1 records from Sudeniederung (Amt Neuhaus). 5 records from Données naturalistes d'Aurélien CABARET. 101 records from Inventaire de la flore des Landes 2017. 1 records from Données naturalistes de AMBEC Nils. 435 records from Lund Botanical Museum (LD). 7 records from Inventaire de la flore du PNRLG 2014 (Landes et Gironde). 23 records from United Herbaria of the University and ETH Zurich. 2 records from Natural History Museum (London) Collection Specimens. 67 records from Vascular plant herbarium (KMN) UiA. 1 records from Ried und Sand - Artenvielfalt durch Beweidung. 3 records from SER Species-based Surveys. 72 records from IBF Monitoring of Vascular Plants. 47 records from River Macrophytes Database. 1 records from Données naturalistes de Philippe GOURDAIN (ANVL). 1 records from Sheffield and Rotherham Wildlife Trust - Records. 12 records from Inventaire de la flore des pelouses littorales de l'estuaire de la Gironde en Charente-Maritime 2012. 1 records from Steinbruch Haas Stuttgart-Münster. 9591 records from Flore du Bassin parisien (CBNBP). 174 records from Jordal. 20 records from Universidad de Barcelona (Facultad de Biología): Plantas vasculares del valle de Son del Pi y áreas colindantes. 1 records from KU E16 Slæn - Tvinno. 102 records from Inventaire de la flore de Lot-et-Garonne 2015. 603 records from Vascular plant field notes, NTNU University Museum. 5 records from Herbarium of Namur. 34 records from Herbário João de Carvalho e Vasconcellos, I.S.A./U.L.. 1 records from Unser kleines Rasenstück/ Dürer-Gymnasium Nürnberg. 31 records from Herbario COFC de la Universidad de Córdoba: colección general de plantas vasculares. 2 records from Urwald 1 (Bad Waldsee). 10946 records from Observations floristiques - plateforme SINP régionale SILENE PACA. 3 records from Espèces Végétales Menacées de France métropolitaine. 1 records from National Plant Monitoring Scheme - Northern Ireland. 1 records from Wildes Bremer Leben im Park. 1 records from Herbarium GB, University of Gothenburg. 1 records from Kalsnava Arboretum Dendrological Collection. 1 records from Inventaire de la Forêt de la Commanderie, Fontainebleau. 1499 records from Shropshire Ecological Data Network database. 122 records from Rotherham Biological Records Centre - Non-sensitive Records from all taxonomic groups. 10 records from Herbario de la Universidad de Almería. 1 records from Tag der Artenvielfalt im Taubental. 9823 records from Dutch Vegetation Database. 1 records from City of Edinburgh Natural Heritage Service - Historical Records. 42 records from Phanerogamic Botanical Collections (S). 209 records from Inventaire de la flore de Gironde 2014. 270 records from Données 'Flore remarquable' du Parc national des Pyrénées. 715 records from Flora-On: occurrence data of the flora of mainland Portugal. 796 records from EDP Foz-Tua: Vascular Flora – Ecological and Complentary Measures Monitoring Programs – Contruction Phase I [2012-2014]. 9 records from CEDaR Online Recording. 2 records from Verneplan Hjerkinn karplanter. 1148 records from RNF - Données de la Fédération des Réserves Catalanes. 377 records from EDP Baixo Sabor: Construction and Reservoir Filling Phases – Vascular Flora and Habitats: species from prioritary conservation habitats - [2010-2014]. 1 records from Gurgltal (Tarrenz). 1 records from Freiburger Tag der Artenvielfalt. 1 records from Vascular plant diversity in forests. 14 records from Leicestershire and Rutland Environmental Records Centre records pre 2000. 1 records from Schulhof der Astrid-Lindgren-Schule (Elmshorn). 24 records from Miscellaneous records held by BIS. 113 records from Wikiplantbase #Italia. 61 records from Jardín Botánico de Córdoba: Herbarium COA. 252 records from Pl@ntNet observations. 4 records from SANT Herbarium vascular plants collection. 114 records from Leicestershire and Rutland Environmental Records Centre records 2010-2014. 1 records from Observations lors des phases de reconnaissance et d'installation (terrestre) - La Planète Revisitée Corse 2019. 1 records from Norwegian Biodiversity Information Centre - Other datasets. 2 records from NABU-Auerochsenweide. 1 records from Données espèces - Expertise IQE 108. 1 records from "Flora of Russia" on iNaturalist: a trusted backlog. 24 records from Inventaire de la flore des Pyrénées-Atlantiques 2014. 2 records from Bergkamen- Bergehalde Großes Holz. 1 records from Wangerooge. 5 records from City of Edinburgh Natural Heritage Service - Ranger Patrol Records. 1 records from Churchyards for London. 109 records from Flora d'Andorra. 160 records from Inventaire de la flore de Gironde 2017. 235 records from National Trust for Scotland Species Records. 96 records from Inventaire de la flore de Lot-et-Garonne 2016. 1 records from Données issues du dispositif de Biosurveillance des Retombées Atmosphériques Métalliques par les Mousses (BRAMM). 12 records from Inventaire de la flore des Deux-Sèvres 2013. 7 records from Data from Defra Family Organisations supplied to Staffordshire Ecological Record. 2 records from Fremmede arter - Planteimport, Engebråten Planteskole. 4 records from The vascular plants collection (P) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 1 records from Artenvielfalt am Schlern. 87 records from Vascular Plant Herbarium, UiB. 1 records from MoJ BioBlitz April - May 2017. 1251 records from SEWBReC Vascular Plants (South East Wales). 7 records from PAMP-tracheo: Vascular plants recovery after a fire event in a mixed oak forest in Nazar (Navarra, Spain). PhD project, L. Alberdi. 4 records from pflanzendiversitaet_2008_sch_alb_hai_aktualisiert. 5 records from RNF - Données de l'association de la RN du lac de Remoray. 1 records from Truppenübungsplatz Panzerkaserne Böblingen. 2 records from Walldorf-Wiesloch: "Natur über den Gleisen". 1 records from FFH-Gebiet Ahrbachtal. 14 records from Phytocenoteca of the laboratory of ecosystem theory (Plants). 2177 records from Scottish SNH-funded BSBI records. 1 records from Herbarium of Taiwan Forestry Research Institute. 2 records from UKSBA Cyprus - Habitat Samples, 2019. 160 records from Merseyside BioBank (verified). 3 records from Monitoring data from the federal state Mecklenburg-Western Pomerania (Germany). 15 records from Données faune, flore et fonge du Conservatoire des espaces naturels de Picardie. 50784 records from Swiss National Databank of Vascular Plants. 1 records from iRecord Surveys. 449 records from VegetWeb - Repositorium von Vegetationsaufnahmen. 2 records from Geschützter Landschaftsbestandteil - GLB "Troppach". 1 records from SWECO. 3550 records from Observations floristiques floutées issues de la base de données flore du Conservatoire botanique national alpin. 7 records from Données naturalistes de Jeanne VALLET. 14 records from Flore du Limousin. 1155 records from Flore Franco-Belge. 12 records from Herbario de la Universidad Pública de Navarra, Pamplona: UPNA-H. 71 records from Finnish Floristic Database (University of Turku Collections). 1 records from UFMT - Herbário UFMT. 1 records from Schatzinsel Wangerooge. 1 records from Données naturalistes de Pierre NOEL (pnoel). 23 records from NRW Regional Data: all taxa (excluding sensitive species), West Wales. 4 records from RNF - Association Loiret Nature Environnement. 6740 records from Waarnemingen.be - Plant occurrences in Flanders and the Brussels Capital Region, Belgium. 7 records from KU Tunnel Kåfjord 2012 - Vegetasjon. 930 records from Carnet en Ligne. 32 records from The Fungal Collection at the Senckenberg Museum für Naturkunde Görlitz. 76 records from Inventaire de la flore de Bordeaux Métropole 2013. 1 records from Données du partenariat Imerys - UMS PatriNat - 2018-2020. 1 records from MEL AVH data. 16 records from RNF - Conservatoire d'espaces naturel Nord-Pas-de-Calais. 13 records from Inventaire de la flore de Charente-Maritime 2013. 39 records from ARKO strandeng. 227 records from Inventaire de la flore de Dordogne 2016. 17 records from Wikiplantbase Sicilia. 1 records from Herbario EMMA. Herbario de la Escuela Técnica Superior de Ingenieros de Montes. UPM. 49 records from Inventaire de la flore des Landes 2014. 11 records from Effects of vegetation clearing on vascular plants in power line clearings southeast Norway. 7 records from Données d'occurrence Espèces issues de la base Natura 2000 : espèces d'intérêt communautaire et autres espèces remarquables renseignées dans les FSD. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences